Assessment of ghrelin serum level and gene polymorphism as a risk factor in progression of chronic viral hepatitis - Lamiaa Mahmoud Kamel; Nagwa Mohamed Shawky; Amal A Jouda; Amany Mohamed Ibrahim; Heba H. Mahboub; Sherif Y. Mohammed (Scientific Reports)
Abstract Hepatocellular carcinoma (HCC) is a significant health concern, ranking as the fourth most common cancer in Egypt and the sixth globally. Research has identified over 300 single nucleotide polymorphisms (SNPs) in the ghrelin gene, with four of these SNPs being associated with pathogenicity. The current work is a pioneer attempt to evaluate the role of Ghrelin gene polymorphism as a risk factor for progression of chronic viral hepatitis to cirrhosis and hepatocellular carcinoma in Egyptian patients. This study was carried out on 80 cases and were allocated into four groups: Group I: apparently healthy individuals, Group II: patients with chronic viral hepatitis, Group III: patients with post-hepatitic cirrhosis, and Group IV: patients with viral hepatitis-related HCC. Serum Ghrelin was measured by ELISA Kit. Molecular detection of Ghrelin rs34911341 and rs696217 were assessed using DNA sequencing. Outcomes showed that in terms of ghrelin gene polymorphism, every group under study had a GG rs34911341. The frequency of rs696217 genotype CA was statistically significantly higher in controls than in cirrhotic and HCC cases. When cirrhosis and HCC cases were compared to controls and chronic active hepatitis cases, the serum ghrelin level decreased statistically significantly. Taken together, there was no relation of ghrelin gene polymorphism in rs34911341 with progression of chronic active hepatitis. Moreover, the frequency of rs696217 genotype CA was increased in controls compared to patients with chronic viral hepatitis and patients with viral hepatitis-related HCC. Compared to controls, liver disease patients had lower serum Ghrelin levels.